Relationship between sleep disorders and the prognosis of neurological function after stroke - Zhang, Yajing; Xia, Xiaoshuang; Zhang, Ting; Zhang, Chao; Liu, Ran; Yang, Yun; Liu, Shuling; Li, Xin; Yue, Wei (Frontiers in Neurology, 2022)
Abstract Objective: To investigate the effect of sleep disorders on the prognosis of neurological function after stroke and other factors affecting the prognosis of neurological function after stroke. Method: A total of 1542 patients with first stroke were hospitalized in department of neurology of Tianjin Huanhu Hospital from 2015.6.1 to 2016.12.31. We recorded the personal history of patients. The MMSE (mini-mental state examination), MoCA (Montreal Cognitive Assessment), HAMD (Hamilton Depression Scale), mRS (Modified Rankin Scale), BI (Barthel index), PSQI (Pittsburgh Sleep Quality Index), ESS (Epworth Sleepiness Scale), Berlin questionnaire, nocturnal TST (Total sleep time) were assessed before discharge, 3 months, 6 months, and 4 years (2019-2020) after stroke. Result: Low sleep quality（OR 2.019 ，95%CI 1.199-3.398, P-0.008）,nocturnal TST(<7h)（OR 4.060 ，95%CI 1.494-3.398, P=0.005）,nocturnal TST(>8h)（OR 5.928，95%CI 2.134-16.464, P=0.001）were risk factors for poor neurological function recovery at 3 months after stroke. Nocturnal TST (<7h) (OR 13.042, 95%-CI 2.576-66.027,P=0.001) and nocturnal TST (>8h) (OR 11.559, 95%-CI 2.108-63.390, P=0.005) were risk factors for poor neurological function at 6 months after stroke. Nocturnal TST(<7h)（OR 2.668, 95% CI 1.250-5.698, P=0.011）and nocturnal TST(>8h)（OR 2.516,95% CI 1.080-5.861, P=0.033）were risk factors for poor neurological function at 4 years after stroke. High risk of OSA（HR 1.582,95%CI 1.244-2.012, P<0.001）was a risk factor for all - cause death in patients followed up for 4 years after stroke. Conclusion: Low sleep quality is associated with the short-term poor neurological function after stroke. Unnormal nocturnal TST(long or short) is associated with short-term or long-term poor neurological function after stroke. High risk of OSA is associated with the risk of all - cause death after stroke.